Bacteria associated with yellow lupine grown on a metal‐contaminated soil: in vitro screening and in vivo evaluation for their potential to enhance Cd phytoextraction. (8th January 2014) - Weyens, N.; Gielen, M.; Beckers, B.; Boulet, J.; van der Lelie, D.; Taghavi, S.; Carleer, R.; Vangronsveld, J.; Papen, H.
Abstract In order to stimulate selection for plant‐associated bacteria with the potential to improve Cd phytoextraction, yellow lupine plants were grown on a metal‐contaminated field soil. It was hypothesised that growing these plants on this contaminated soil, which is a source of bacteria possessing different traits to cope with Cd, could enhance colonisation of lupine with potential plant‐associated bacteria that could then be inoculated in Cd‐exposed plants to reduce Cd phytotoxicity and enhance Cd uptake. All cultivable bacteria from rhizosphere, root and stem were isolated and genotypically and phenotypically characterised. Many of the rhizobacteria and root endophytes produce siderophores, organic acids, indole‐3‐acetic acid (IAA) and aminocyclopropane‐1‐carboxylate (ACC) deaminase, as well as being resistant to Cd and Zn. Most of the stem endophytes could produce organic acids (73.8%) and IAA (74.3%), however, only a minor fraction (up to 0.7%) were Cd or Zn resistant or could produce siderophores or ACC deaminase. A siderophore‐ and ACC deaminase‐producing, highly Cd‐resistant Rhizobium sp. from the rhizosphere, a siderophore‐, organic acid‐, IAA‐ and ACC deaminase‐producing highly Cd‐resistant Pseudomonas sp. colonising the roots, a highly Cd‐ and Zn‐resistant organic acid and IAA‐producing Clavibacter sp. present in the stem, and a consortium composed of these three strains were inoculated into non‐exposed and Cd‐exposed yellow lupine plants. Although all selected strains possessed promising in vitro characteristics to improve Cd phytoextraction, inoculation of none of the strains (i) reduced Cd phytotoxicity nor (ii) strongly affected plant Cd uptake. This work highlights that in vitro characterisation of bacteria is not sufficient to predict the in vivo behaviour of bacteria in interaction with their host plants.